2023
DOI: 10.1039/d2cc06371a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of maleimide-braced peptide macrocycles and their potential anti-SARS-CoV-2 mechanisms

Abstract: Peptidomimetic macrocycles often exhibit superior biological properties and druggability, leading to their versatile application in the pharmaceutical industry. A highly efficient and practical methodology for the functionalization and macrocyclization of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, both WWNLN and WAVLK possess tryptophan (Trp) at the N-terminal. As known, Trp is one of the essential amino acids and it plays an important role in protein synthesis and metabolic regulation in the body. , The indole moiety in Trp could form hydrogen bonds, hydrophobic interaction, cation–π interaction, metal coordination, π–π interaction, and π–alkyl/sulfur interaction with protein, which is critical in the construction of versatile peptides with diverse structural and biophysical properties. To confirm this, detailed interactions between WWNLN/WAVLK and M pro in their representative conformations were illustrated by Discovery Studio Visualizer (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, both WWNLN and WAVLK possess tryptophan (Trp) at the N-terminal. As known, Trp is one of the essential amino acids and it plays an important role in protein synthesis and metabolic regulation in the body. , The indole moiety in Trp could form hydrogen bonds, hydrophobic interaction, cation–π interaction, metal coordination, π–π interaction, and π–alkyl/sulfur interaction with protein, which is critical in the construction of versatile peptides with diverse structural and biophysical properties. To confirm this, detailed interactions between WWNLN/WAVLK and M pro in their representative conformations were illustrated by Discovery Studio Visualizer (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Take the last 3 years for instance, transition-metal-catalyzed C-H activation provides distinct peptide late-stage modication with good chemoselectivity, which has been explored by several groups. [22][23][24][25][26][27][28][29][30] However, the reported methods require harsh reaction conditions, such as high temperatures, oxidant additives, auxiliary directing groups, and complex reaction conditions, which restrict their application prospects in bioactive peptide research. With the development of photochemistry in recent years, radicalmedicated C2 amination, [31][32][33] uoroalkylation, 34,35 alkylation, 36,37 and thiation 38,39 on the indole ring of tryptophan have been explored for the functionalization of peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, transition-metal-catalyzed C–H activation has emerged as a powerful strategy for the synthesis and late-stage modification of complex peptides. It has also become a straightforward process for the preparation of cyclic peptides, as demonstrated by the work of Albericio/Lavilla, Wang, Ackermann, Liu, and other researchers . Among the native amino acids, the Trp residue has a unique interaction with the protein surface and the hydrophobic side chain.…”
mentioning
confidence: 99%
“…Therefore, the site-directed modification of Trp is highly significant, and it may facilitate the discovery of novel biological peptide structural entities. However, C–H modifications and peptide macrocyclization of Trp are restricted to the C2 position due to their inherent reactivity, and only limited investigations concentrate on the modification of Trp­(C4–C7). , Recently, several indole C7-directing groups, such as N -pivaloyl, N -py­(m), N -P t Bu 2 , N -P­(O) t Bu 2 , and N -SMe, have been reported to provide efficient strategies for Trp­(C7) derivation. Ackermann et al reported Trp­(C7) amidation via Rh­(III)-catalyzed late-stage peptide modification while using N -pyridyl or N -pyrimidyl as the directing group (Figure b) .…”
mentioning
confidence: 99%
See 1 more Smart Citation